Household food security in Misamis Occidental - Malaga, Jenny C.
This study identified the characteristics of the 573 households who have high probability of becoming hungry in each municipalities of Plaridel, Lopez Jaena, Sapang Dalaga, Panaon, Calamba, Aloran, Baliangao, Jimenez and Oroquita City in Misamis Occidental province. Since this study utilized secondary cross sectional data, the choice of variables and the areas included in the study was mainly limited to the variables and areas covered by the data source. The study focused on socio-economic attributes of the households in relation to their food access. The method of Maximum Likelihood estimation was used to obtain the estimates of the constructed logit model. The results showed that for each municipality different combination of socio-economic attributes significantly influence the odds ratio favouring the event of becoming food secure thereby supporting the need for a decentralized, location specific approach to the identification of food insecure and vulnerable groups. The condition of a household with adults attaining only elementary level education appeared to be the most common attribute of being food insecure among five municipalities. Ownership of appliance and livestock assets also appeared to be positively influencing the probability of becoming food secure.